Quasi-phase-matching of high-harmonic generation - Robinson, T; Thomas Robinson (2009)
This thesis describes the use of counterpropagating pulse trains to quasi-phase-match high-harmonic generation (HHG). Two novel techniques for generating trains of ultrafast pulses are described and demonstrated. The first method makes use of a birefringent crystal array to split a single pulse into a sequence of pulses. The second method makes use of the time-varying polarisation of a chirped pulse passed through a multiple-order wave plate to generate a train of pulses by the addition of a polariser. It is demonstrated that this second technique can be used to make pulse trains with non-uniform pulse separation by using an acousto-optic programmable dispersive filter to manipulate the higher-order dispersion encountered by the chirped pulse. The crystal array method is used to demonstrate quasi-phase-matching of HHG in a gas-filled capillary, using one and two counterpropagating pulses. Enhancements of up to 60% of the intensity of the 27th harmonic of the 800,nm driving laser light are observed. Information on the spatial and dynamic properties of the HHG process is obtained from measurements of the coherence length in the capillary. Simulations of HHG in a capillary waveguide have been performed. These agree well with the results of the quasi-phase-matching experiments. The effect of mode-beating on the generation process in a capillary and its use as a quasi-phase-matching mechanism are investigated.